Penerapan Focus Group Discussion (FGD) untuk Meningkatkan Pemahaman Siswa Sekolah Dasar Tentang Bahaya Konsumsi Mi Instan (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
Instant noodles are one of the people's favorite foods in many countries, including Indonesia. ). Theresults of a survey by the Indonesian Consumers Foundation on 600 parents of kindergarten andelementary school students in five areas in Jakarta in 2014, showed that 93% of respondents stated thatthey often consumed instant noodles during the week. The aim of this research is to determine theapplication of Focus Group Discussion (FGD) in increasing elementary school (SD) students'understanding of the dangers of consuming instant noodles. The method used in this research isqualitative. The habit of consuming instant noodles before the FGD was carried out was that severalstudents consumed more than one pack of instant noodles in one day. The correct pattern of instantnoodle consumption was able to be explained by all respondents. The conclusion of this research is thatthe understanding that elementary school students have after participating in the FGD shows changes ina good direction is reduce consumption of instant noodles.
Keywords: FGD; Understanding; Danger; Instant Noodle